The Spread of COVID-19 Among 15, 000 Physical Therapists in Italy: A Cross-Sectional Study. Issue 8 (8th May 2021) - Gianola, Silvia; Bargeri, Silvia; Campanini, Isabella; Corbetta, Davide; Gambazza, Simone; Innocenti, Tiziano; Meroni, Roberto; Castellini, Greta; Turolla, Andrea; ,
Abstract: Objectives: The purpose of this study was to explore the prevalence, personal- and work-related exposures, and signs and symptoms among physical therapists during the first wave of coronavirus disease 2019 (COVID-19) in Italy. Methods: This cross-sectional, survey-based study collected demographic and exposure data from physical therapists from April to May 2020. All physical therapists working in inpatient and outpatient care in Italy were eligible. A self-administered questionnaire was distributed among all eligible physical therapists to collect (1) demographic characteristics, (2–3) personal- and work-related exposures, and (4) signs and symptoms of COVID-19. Factors associated with a COVID-19–positive nasopharyngeal swab (NPS) were explored through logistic regression models and multivariate methods. Results: A total of 15, 566 respondents completed the survey, with a response rate of 43.3%, achieving high statistical precision (99% CI, 1% type I error). Among physical therapists who received NPS testing, 13.1% (95% CI = 12.1–14.1%) had a positive result, with a peak reached in March 2020 (36%). The top 5 symptoms were fatigue and tiredness (69.1%), loss of smell (64.5%), aches and pains (60.8%), loss of taste (58.3%), and headache (51.1%). No symptoms were reported by 8.9%. Working in a health care institution (odds ratio [OR] = 12.0; 95% CI = 7.8–18.4), being reallocated to a different unit (OR = 1.9; 95% CI = 1.3–2.7), and changing job tasks (OR = 1.6; 95% CI = 1.2–2.3) increased the risk of being COVID-19 positive. In therapists with a confirmed diagnosis of COVID-19, comorbidities were associated with male sex and age older than 51 years. Conclusion: During the first wave in Italy, almost 1 out of 7 physical therapists tested positive on the COVID-19 NPS test. Considering personal- and work-related exposures, health care organizations should adopt prevention measures and adequate preparedness to prevent high rate of infections during future pandemics. Impact: This is the largest investigation about the spread of and main risk factors for COVID-19 in the physical therapy field.